Managers' psychological diversity climate and fairness: The utility and importance of diversity management in the hospitality industry. Issue 3 (3rd July 2017) - Madera, Juan M.; Dawson, Mary; Neal, Jack A.
ABSTRACT: Despite corporate investments in diversity management programs, there is a dearth in the literature that examines managers' attitudes toward diversity management practices. This is a glaring gap in the literature because the success of diversity management programs is highly depend on managers. A survey was distributed to hotel managers from properties in the southern United States. The results showed that psychological diversity climate predicted the perceived utility and importance of diversity management, and these relationships were mediated by the fairness of diversity management. These results suggest that psychological diversity climate has an impact on attitudes toward diversity management practices.